A Bis(guanidinium)alcohol Attached to a Hairpin Polyamide: Synthesis, DNA Binding, and Plasmid Cleavage. (16th February 2016) - Wirth‐Hamdoune, Daniela; Ullrich, Stefan; Scheffer, Ute; Radanović, Toni; Dürner, Gerd; Göbel, Michael W.
Abstract: Bis(guanidinium)alcohols have been designed to react with phosphodiester substrates in a fast transphosphorylation step, a quasi‐intramolecular process taking place in contact ion pairs. Here the attachment of such compounds to Dervan‐type hairpin polyamides is described. The resulting conjugate 1 binds to AT‐rich DNA duplexes with affinity similar to that of the parent polyamide as shown by UV melting experiments and CD titrations. Conjugate 1 nicks plasmid DNA at concentrations ranging from micromolar to high nanomolar. Abstract : Nicked ! A cationic alcohol designed to form ion‐pair complexes with phosphate diesters and to react by nucleophilic displacement has been attached to a DNA‐binding Dervan‐type hairpin polyamide. The resulting conjugate nicks plasmid DNA at concentrations ranging from micromolar to high nanomolar.